Use of in vitro methodology to investigate phthalate effects on the differentiation of seminiferous tubule-associated stem cells to form Leydig cells and on the Leydig cells derived from the stem cells - Kassim Traore; Kassim Traore; Barry Zirkin (Frontiers in Toxicology, 2024)
Introduction: Leydig cells isolated from the testis are able to sustain high levels of testosterone production in vitro, but only for up to 3 days. Such cells are valuable for addressing the acute effects of chemicals on steroidogenic function, but not for repeated or chronic effects. Methodology is now available by which adult Leydig cells can be derived in vitro from seminiferous tubule-associated stem cells. In contrast to isolated Leydig cells, the Leydig cells derived in this way can synthesize and secrete high levels of testosterone for months. Herein, we asked whether this system might be used to address the effect of mono-(2-ethylhexyl) phthalate (MEHP) exposure on the formation of Leydig cells from tubule-associated stem cells, and on the Leydig cells after their formation.Methods: Adult Brown Norway rats received an intraperitoneal injection of ethane dimethanesulfonate (EDS) to eliminate the existing Leydig cells. Seminiferous tubules then were isolated and cultured in medium containing Insulin-Transferrin- Selenium (ITS), Smoothened Agonist (SAG), and luteinizing hormone (LH).Results: Culture of the tubules for 8 weeks resulted in the formation of cells on the surfaces of the tubules that stained for CYP11A1 and STAR and produced high levels of testosterone. When the tubules were cultured in medium containing increasing concentrations of MEHP, concentration-dependent effects on Leydig cell formation occurred. To determine the effect of MEHP on newly produced Leydig cells, tubules were cultured for 8 weeks in the absence of MEHP, resulting in the formation of adult Leydig cells, and then in medium containing increasing concentrations of MEHP. Concentration-dependent decreases in testosterone production by the adult Leydig cells were seen, and these decreases proved to be reversible.Discussion: The use of this new system should make it possible to determine the mechanisms by which acute, repeated, or chronic exposures to increasing concentrations of MEHP and/or exposure to other chemicals affect the formation of Leydig cells from stem cells, as well as the steroidogenic function of adult Leydig cells.